Peran Kelenjar Hipofisis dan Pengaruh Neuroendokrin terhadap Perilaku Manusia: Telaah Literatur Sistematik - Siti Nur Asiyah Maskan; Imroatun Najihan; Khanifa Aulia Ayu Devinadia; Mohammad Raynugroho; Naila Syifaun Najmi; Nella Andin Rinjani; Putri Juliantika; Rifdha Nur Shafa; Risma Dwi Rahmadhani; Febryan Tri Pamungkas Saraswanto (Majalah Kedokteran Indonesia, 2025)
Human behavior is shaped by the complex interaction between the nervous and endocrine systems. The pituitary gland, as a major component of the endocrine system, plays a crucial role in regulating both physiological and psychological functions through the secretion of various hormones. This study aims to systematically review the role of the pituitary gland and the influence of the neuroendocrine system on human behavior. The research employed a Systematic Literature Review (SLR) method, analyzing eight selected scientific articles published between 2021 and 2025. Articles were sourced from Google Scholar, ScienceDirect, and ResearchGate using relevant keywords, and filtered following PRISMA guidelines. The review revealed that pituitary-secreted hormones such as ACTH, GH, prolactin, LH, FSH, and oxytocin have significant impacts on stress regulation, emotions, social bonding, and cognitive functions. The hypothalamic–pituitary–adrenal (HPA) axis plays a central role in the stress response and is strongly linked to psychological symptoms including anxiety and depression. Additionally, non-pharmacological interventions such as music therapy have been shown to stabilize neuroendocrine activity and effectively reduce anxiety. The pituitary gland functions as a hormonal control center that influences various aspects of human behavior. This review underscores the importance of neuroendocrine understanding within psychological contexts and supports the development of physiological-based interventions for mental well-being.